THE DEVELOPMENT OF SCIENTIFIC APPROACH-ORIENTED SCIENCE LEARNING MATERIALS ON BIOTECHNOLOGY AND FOOD PRODUCTION TOPICS FOR GRADE IX JUNIOR HIGH SCHOOL - Febrina, Ririn Febrina Ririn; Natalina, Mariani Natalina Mariani; Suryawati, Evi Suryawati Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research was to develop scientific approach-oriented science learning materials on biotechnology and food production topic for grade IX junior high school. The developments consisted of syllabus, lesson plans, worksheets, authentic assessment (paper and pencil test, attitude assessment, performance assessment, product assessment, project assessment, self-assessment and portofolio assessment). The development was conducted at Biology Education University of Riau and the pilot test at SMPN 7 Pekanbaru. The research held on April until December 2014. Research and Development with ADDIE model was implemented in this research The subjects were Basic Competence 3.9 and 4.9 that containing in the grade IX Junior High School. Validation sheet was used as data collecting instrument. Validation sheet was filled by four validators. Data were analyzed by descriptive statistics. The results of the development of science learning materials obtained the following data: lesson plan was 3.6, student worksheet was 3.6, attitude assessment was 3.6, the project assessment was 3.7, the product assessment was 3.6, the performance assessment was 3.6, a written assessment was 3.5, self-assessment was 3.6, portofolio assessment was 3.8. In the final stage of research, limited test was conducted using the worksheets, student response  questionnaires and self-assessment questionnaires on class IX.7 with 34 students. Based on the results of the validation and pilot test, it can be conclude that the scientific approach-oriented science learning materials for grade IX junior high school could be implement throught the field-scale test. Keywords:biotechnology, food production, scientific approach, natural science learning material